2017
DOI: 10.5604/01.3001.0010.0293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, and Survival of Patients with Intrahepatic Cholangiocarcinoma

Abstract: We found an overall prevalence of intrahepatic cholangiocarcinoma of 7.7%; unfortunately, these patients were diagnosed at advanced stages. Smoking and primary sclerosing cholangitis were the positive risk factors for its development in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…13 Currently, early diagnosis of HL-CCA in clinical setting is still challenging even though there have been advances in diagnostic modalities and various efforts to identify it in early stages. 14 It has been known that miRNAs are involved in almost all life activities of cells including cell proliferation, differentiation and apoptosis. 15,16 Recent studies have shown that the miRNA expression level may be related to cancers.…”
Section: Discussionmentioning
confidence: 99%
“…13 Currently, early diagnosis of HL-CCA in clinical setting is still challenging even though there have been advances in diagnostic modalities and various efforts to identify it in early stages. 14 It has been known that miRNAs are involved in almost all life activities of cells including cell proliferation, differentiation and apoptosis. 15,16 Recent studies have shown that the miRNA expression level may be related to cancers.…”
Section: Discussionmentioning
confidence: 99%
“…ICC is the second most common histologic type of liver malignant tumor.16 The incidence and mortality of ICC are steadily on the rise worldwide. Accurate and efficient information on prognosis is important for both clinicians and patients to make an individualized treatment decision.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate preoperative differentiation of ICC and HCC has always been limited because of the similar imaging signs depicted by using the usual imaging modalities can not be used to accurately differentiate these entities [ 14 , 15 ]. HCC usually coexists with liver cirrhosis, whereas ICC is traditionally considered to mainly in the absence of cirrhosis and which used to be regarded as the differential diagnosis point [ 22 , 23 ]. However, ICC can also be presented with cirrhosis especially with the risk factor of HBV infection, so the differentiation of ICC and HCC can be much more difficult in the cirrhotic livers.…”
Section: Discussionmentioning
confidence: 99%